2014
DOI: 10.1186/s13030-014-0027-8
|View full text |Cite
|
Sign up to set email alerts
|

Isometric yoga improves the fatigue and pain of patients with chronic fatigue syndrome who are resistant to conventional therapy: a randomized, controlled trial

Abstract: BackgroundPatients with chronic fatigue syndrome (CFS) often complain of persistent fatigue even after conventional therapies such as pharmacotherapy, cognitive behavioral therapy, or graded exercise therapy. The aim of this study was to investigate in a randomized, controlled trial the feasibility and efficacy of isometric yoga in patients with CFS who are resistant to conventional treatments.MethodsThis trial enrolled 30 patients with CFS who did not have satisfactory improvement after receiving conventional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(57 citation statements)
references
References 25 publications
(18 reference statements)
1
55
0
Order By: Relevance
“…DiStasio stated that patients with symptomatic anemia, orthostatic hypotension, and lightheadedness should avoid prolonged standing poses, that cancer patients with fever and systemic infection should avoid vigorous yoga poses [ 37 ], and that patients with signs of osteoarthritis are not recommended to do yoga [ 5 ]. Since individuals with various chronic diseases practice yoga, it is important for these individuals to let the yoga therapists know in advance about their diseases [ 36 , 38 ]. Certain yoga poses or the practice of yoga itself might be prohibited or not recommended for individuals with certain conditions or diseases.…”
Section: Discussionmentioning
confidence: 99%
“…DiStasio stated that patients with symptomatic anemia, orthostatic hypotension, and lightheadedness should avoid prolonged standing poses, that cancer patients with fever and systemic infection should avoid vigorous yoga poses [ 37 ], and that patients with signs of osteoarthritis are not recommended to do yoga [ 5 ]. Since individuals with various chronic diseases practice yoga, it is important for these individuals to let the yoga therapists know in advance about their diseases [ 36 , 38 ]. Certain yoga poses or the practice of yoga itself might be prohibited or not recommended for individuals with certain conditions or diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous randomized controlled trial, we demonstrated that sitting isometric yoga improved fatigue and pain in patients with CFS who were resistant to conventional therapy [ 2 ]. In this trial, the Chalder fatigue score in patients who, in addition to receiving conventional pharmacotherapy, practiced 20-min of sitting isometric yoga for two months was significantly lower than in patients who received conventional therapy alone.…”
Section: Introductionmentioning
confidence: 99%
“… 18 Several other studies also reported an improvement in the “fatigue” dimension of the POMS-SF as a result of physical activity. 19 , 20 However, these studies differed from the present study in that they included subjects with some type of disorder. It has been reported that levels of habitual physical activity are lower in older adults with greater self-reported fatigue.…”
Section: Discussionmentioning
confidence: 74%